Where Boys, Girls and Children Come From - Hlebec, Boris (Studia Anglica Posnaniensia, 2013)
The etymology of three very frequent English words child, girl and boy has been notoriously obscure because researchers have failed to pay attention to possible Slavic influence. This article is aimed at rectifying this major oversight by providing abundant evidence of both formal and semantic similarities between the English items and the corresponding Slavic ones and at establishing Scandinavian as an intermediary for girl and boy, no such connector being necessary for child.